2022
DOI: 10.3389/fpsyt.2022.931558
|View full text |Cite
|
Sign up to set email alerts
|

The co-occurrence of multidimensional loneliness with depression, social anxiety and paranoia in non-clinical young adults: A latent profile analysis

Abstract: IntroductionLoneliness is a negative experience arising from a mismatch between perceived and actual social relationships. Several dimensions of loneliness have been suggested, namely intimate, relational and collective loneliness. Loneliness has been linked to poorer mental health, with its co-occurrence with depression, social anxiety, and paranoia most widely reported. While expressions of these symptoms are heterogeneous across individuals in the non-clinical population, it remains unclear how these sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Through the ‘compensatory Internet use mode’, Kardefelt-Winther puts forward the reason why loneliness leads to mobile phone addiction, that is, people will use mobile phones to escape real-life problems and alleviate negative emotions (including loneliness) [ 63 ]. Moreover, lonely people also experience more anxiety [ 64 , 65 ]. In contrast, most rural adolescents, whose parents work outside the home, live with their grandparents.…”
Section: Discussionmentioning
confidence: 99%
“…Through the ‘compensatory Internet use mode’, Kardefelt-Winther puts forward the reason why loneliness leads to mobile phone addiction, that is, people will use mobile phones to escape real-life problems and alleviate negative emotions (including loneliness) [ 63 ]. Moreover, lonely people also experience more anxiety [ 64 , 65 ]. In contrast, most rural adolescents, whose parents work outside the home, live with their grandparents.…”
Section: Discussionmentioning
confidence: 99%
“…The translation and back-translation were conducted independently by bilingual, graduate-level psychologists. Comparison of the original v. back-translated version and decisions for final changes were based on consensus between the (Chau et al, 2022), where it showed an excellent Cronbach's alpha (α = 0.95). The German and Traditional Chinese versions of the R-GPTS have been added as an online Supplement to this article.…”
Section: R-gptsmentioning
confidence: 99%